Go Ape case study (Part A): monkeying around? - Hussels, Stephanie; Molian, David (Senate Hall, 2010)
The case study tells the story of GoApe!, a fast-growth entrepreneurial success story started in 2002 by the husband and wife team of Tristram and Rebecca Mayhew. The case study is split into Parts A and B. Part A poses the question whether the couple should abandon well-paid corporate careers and take a step into the unknown to realise their dream of living in the country and achieving a better balance between their family life and earning their living. They have identified a unique opportunity to take an outdoor leisure concept developed in France and introduce it into the UK, in partnership with the British Forestry Commission. This particular opportunity will allow them to create a business which is sustainable, environmentally responsible and in line with the couple's values and beliefs. At the end of part A their dilemma is should they start the business and give up corporate life, play safe and commission market research, or take the chance of a lifetime. A detailed Teaching Note with an analysis and suggestions for questions is also available to stimulate discussion in the classroom. GoApe! was a category winner in the 2009 UK National Business Awards, the most prestigious awards ceremony of its kind organised in partnership with Orange. Keywords: entrepreneurship, new venture creation, sustainability, sources of finance, start-up valuations, UK
Keywords: entrepreneurship|managing growth|sustainability|sources of finance|start-up valuations|UK